Preservation and Promotion of Periodicals in the National Library of the Republic of Sakha (Yakutia) - Pyotr P. Gorokhov; Петр Петрович Горохов (Russian State Library, 2024)
In the context of the national cultural heritage the author considers the urgent problem of preservation of library collections on the example of the National Library of the Republic of Sakha (Yakutia) (NL RS (Ya)). The author emphasizes the key role of the library in working with periodicals of Yakutia as part of the documentary heritage of the peoples of Russia. Periodicals of Yakutia are an important component of the national and local history collection of the NL RS (Ya). From the standpoint of source study, periodicals are valuable historical, cultural and book studies material. At the same time, newspapers and magazines, especially the retrospective part of periodicals, are subject to the most severe physical deterioration. At present, the library is carrying out a whole range of works aimed at saving the collection of periodicals in Yakutia.The NL RS (Ya) won the All-Russian open competition of the Russian State Library among the libraries of the constituent entities of the Russian Federation for the establishment of the Regional Conservation and Restoration Centre. The Regional Centre of Conservation and Restoration was opened in Yakutsk on 10 October 2024.The article presents in detail the projects “Give new life to Yakutia’s newspapers” and “Bibliography of the content of local history periodicals of Yakutia” implemented by the library. Special attention is paid to the library’s work on creating conditions for full and open access for readers to the entire collection of periodicals of Yakutia. Examples of using modern technologies in the library environment are given. Digitalization and introduction of artificial intelligence will make the work on preservation and promotion of the cultural heritage of the region more effective. The initiatives undertaken by the NL RS (Ya) may be useful for other libraries in Russia. В контексте национального культурного наследия на примере деятельности Национальной библиотеки Республики Саха (Якутия) (НБ РС (Я)) рассматривается актуальная проблема сохранности ...